Measuring the Quality of Early Childhood Education in Low- and Middle-Income Countries - Chen, Si; Wolf, Sharon (Frontiers in Psychology, 2021)
Young children’s access to early childhood education (ECE) is increasing in low- and middle-income countries, though often without attention to service quality. Monitoring quality requires classroom observations, but most observation tools available were developed in high-income Western countries. In this article, we examine key issues in measuring ECE quality in low- and middle-income countries and consider challenges and opportunities in balancing theoretical grounding, cultural- and contextual-adaptation, and empirical rigor. We then review the literature on observed classroom quality in low- and middle-income countries, focusing on process quality. We find limited evidence that the constructs identified in high-income countries replicate in low- and middle-income countries. Further, the very limited evidence that ECE quality measures used in low- and middle-income countries predict child outcomes is almost exclusively cross-sectional and associations are mixed. We conclude by discussing how future research can build a stronger knowledge base about ECE quality and child development globally.